A low loading of grafted thermoplastic polystyrene strengthens and toughens transparent epoxy composites. Issue 17 (13th April 2017) - Gu, Hongbo; Ma, Chao; Liang, Chaobo; Meng, Xudong; Gu, Junwei; Guo, Zhanhu
Abstract : Transparent epoxy composites strengthened and toughened by thermoplastic polystyrene grafted with epichlorohydrin ( g -PS) have been prepared at low loading levels. Abstract : Transparent epoxy composites strengthened and toughened by thermoplastic polystyrene grafted with epichlorohydrin ( g -PS) have been prepared at low loading levels. The polymer backbone of PS was manipulated by the epoxide and hydroxyl groups confirmed by Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and X-ray photoelectron spectroscopy (XPS). Contact angle and differential scanning calorimetry (DSC) tests indicated that the grafting process could decrease the surface tension and increase the compatibility between PS and epoxy resins. The effects of g -PS loading and the grafting process on both the viscosity of liquid epoxy resin suspensions as well as the physicochemical properties of cured epoxy composites have been systematically investigated. The cured g -PS/epoxy composites demonstrated an enhanced tensile strength (maximum of 97.4 MPa) compared to either cured pure epoxy (77.6 MPa) or PS/epoxy composites (79.1 MPa). The modulus of toughness for g -PS/epoxy composites reaches values of up to 355.9 MJ m −3, which is respectively 176.6 and 141.1% higher than those for cured pure epoxy and PS/epoxy composites. The uniform g -PS distribution in the cured g -PS/epoxy composites was observed by scanning electron microscope (SEM). The glass transition temperature ( T g ) of cured g -PS/epoxy composites was shifted to a higher temperature (increased by 16.3 °C) in the dynamic mechanical analysis (DMA) compared with that of cured pure epoxy (111.7 °C). The strong interfacial interaction obtained between g -PS and the epoxy matrix was responsible for the enhanced mechanical and thermal mechanical properties. This work provides a new insight into the investigation of interaction and compatibility between thermoplastic and thermoset materials.